VARIASI SIFAT FISIKA KAYU KEMIRI (Aleurites moluccana) BERDASARKAN ARAH AKSIAL - Simangunsong, Arnita Sari; Hapid, Abdul; Muthmainnah, Muthmainnah (Universitas Tadulako, 2016)
chemical characters were factors as base in choosing wood. Besides knowledge about base characters, wood possessed varies characters even in one tree. This research aimed to find out the physical character that covered water content, density, and dimension change of candlenut wood (Aleurites moluccana) based on axial direction. The research was conducted on May up to the month of July 2014. In Agrotechnology, Forestry Faculty, Tadulako University, Palu. The wood that used as sample was one which about 10 years old with 39 cm diameter and 20 m tall that derived from Ranteleda village, Palolo, Sigi District. The research applied complete random design (Rancangan acak lengkap (RAL) with 3 treatments (butt, middle, top). The test of the sample was based on British Standart 373 each 126,808%, 127,367%, 145,213% and the average of dry air on butt, middle and top were 12,78%, 14,11%, and 12,35%. The rate of wet density was 0,339, dry air density was 0,345 and oven dry density was 0,354. The rate of longitudinal, tangential and radial diminution from wet to dry air was 0,71%, 1,909%, 1,808% and from wet to oven dry was 0,362%, 4,086%, 3,618%. The rate of longitudinal, tangential, and radial expansion from oven dry to wet was 0,107%, 3,491 %, 3,111% Key words: Water Content, Density, Dimension Changes.